Energy use and urbanization as determinants of China's environmental quality: prospects of the Paris climate agreement. Issue 13 (11th October 2022) - Khan, Irfan; Hou, Fujun; Zakari, Abdulrasheed; Tawiah, Vincent; Ali, Syed Ahtsham
Abstract : Climate change is an environmental problem that humanity will face over the next several decades. Environmental quality has always been an important component of the quality of life. The rapid rise in urbanization and energy use in China has profound environmental consequences. This study investigates the impact of energy use and urbanization on China's ecological footprint and CO2 emissions from 1971 to 2016. The results reveal the positive relationship between China's energy use and urbanization, while international trade and capital formation are adversely associated with its CO2 emissions and ecological footprint. Overall, energy use and urbanization deteriorate China's environmental quality, while international trade and capital formation improve it. The results of Granger causality show bidirectional causality between urbanization and ecological footprint and between ecological footprint and CO2 emissions, while unidirectional causality runs from the ecological footprint to energy use and from international trade to the ecological footprint.